Pengembangan Buku Suplemen Berbasis Cerita Bergambar pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar - Norholis, Norholis; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research and development aims to produce a supplementary book product based on illustrated stories in the subject of IPAS on the material of Indonesia's cultural wealth in class IV Elementary School which is feasible to use to assist the learning process in the independent curriculum. The method used is the Research and development (R&D) method by adapting the ADDIE model. 3 expert validators, 3 classroom teachers in the classroom, and 94 students were sampled in this study. strategies for collecting data through questionnaires and interviews. The results of research and development obtained a validity assessment according to the material expert validator in the content/material aspect obtained a percentage value of 82.23% with the criteria